Silk fibroin scaffold as a potential choice for female pelvic reconstruction: A study on the biocompatibility in abdominal wall, pelvic, and vagina. Issue 3 (21st March 2016) - Chang, Yue; Sun, Xiuli; Li, Qi; Ding, Xili; Liu, Haifeng; Wang, Jianliu
ABSTRACT: The aim of this study was to compare the tissue reactions to silk fibroin scaffolds in the abdominal wall, vagina, and pelvic vesico‐uterine of rats. Silk fibroin scaffolds were implanted subcutaneously in the abdominal, pelvic vesico‐uterine space, and under the vaginal mucosa of 16 rats. The animals were euthanized at 2, 4, 8, and 12 weeks postoperatively. Hematoxylin and eosin staining was performed to evaluate cellular infiltration, the percentage of macrophages and granulocytes inside and around the scaffolds. The amounts of M1/M2 macrophages at the interface of scaffolds and host tissue were evaluated through an immunofluorescence assay. The degree of acute inflammation was similar among the three groups, and lasted no more than 4 weeks. A faster ingrowth of fibroblasts was found in the abdominally implanted silk fibroin scaffolds, while vaginal implanted scaffolds committed a slower tissue ingrowth rate and much more macrophages infiltration than the pelvic and abdominal group. However, a significantly higher amount of M2 cells were seen in the three groups. In general, silk fibroin has nice biocompatibility in the abdominal, vagina, and pelvic tissue, eliciting healthy tissue formation, and might be a potential choice for female pelvic reconstruction. Microsc. Res. Tech. 80:291–297, 2017. © 2016 Wiley Periodicals, Inc.